2007
DOI: 10.1016/j.surfcoat.2007.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Air plasma sprayed thermal barrier coatings on titanium alloy substrates

Abstract: Titanium alloys as lightweight structure materials have been shown more interest in the use at moderately elevated temperatures. However, their poor oxidation resistance at temperature above 600°C limits a wide application. Consequently, thermal protection becomes a concern. 8 wt. % yttria partially stabilized zirconia thermal barrier coatings (TBCs) were air plasma sprayed on titanium alloy substrates (Ti-6.6Al-3.61Mo-1.69Zr-0.28Si in wt.%). The microstructures and mechanical properties of the coating system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…This theory is based on an exponential law of a decreasing defect size distribution. And the two-parameter Weibull distribution function is described as: p = 1 À exp[À(x/x 0 ) m ], where x 0 is known as the scale parameter where the probability of occurrence is 63.2% and m is the Weibull modulus (Ref [16][17][18]. The magnitude of m increases with decreasing scatter.…”
Section: Nano-hardnessmentioning
confidence: 99%
“…This theory is based on an exponential law of a decreasing defect size distribution. And the two-parameter Weibull distribution function is described as: p = 1 À exp[À(x/x 0 ) m ], where x 0 is known as the scale parameter where the probability of occurrence is 63.2% and m is the Weibull modulus (Ref [16][17][18]. The magnitude of m increases with decreasing scatter.…”
Section: Nano-hardnessmentioning
confidence: 99%
“…Atmospheric plasma spraying ͑APS͒ remains one of the most used techniques for increasing the maximum service temperature, while thermal barrier coating ͑TBC͒ is an alternative approach. 20 Meng et al worked with laser cladding coatings of NiCoCrAlY on Ti6Al4V and confirmed that it is possible to produce layers with a good metallurgical bond with the substrate and without cracks or pores. Moreover, the substrate becomes twice as hard and more resistant to erosion.…”
Section: Improved Resistance To High Temperaturesmentioning
confidence: 98%
“…Weibull distribution, which is fit for the broad and dispersive distribution of microhardness for brittle ceramic material, was used to analyze microhardness values of TiN-matrix coating. The Weibull distribution of two parameters is given as follows 17 :…”
Section: Microstructure Observation and Property Testsmentioning
confidence: 99%